2007
DOI: 10.1055/s-2007-986686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Electroencephalography and Magnetic Resonance Imaging Findings after Hypoxic-Ischemic Encephalopathy at Term

Abstract: Hypoxic-ischemic encephalopathy (HIE) is a major cause of neonatal morbidity and mortality. Electroencephalography (EEG) and brain magnetic resonance imaging (MRI) are frequently performed in these infants, but the prognostic value of the combined use of EEG and MRI needs additional exploration. The purpose of this study was to investigate, in neonates with HIE, the role of early EEG and conventional MRI in the prediction of infants at risk for persistent encephalopathy at 18 months of age. Thirty-four term in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…In some studies, the value of conventional cranial MRI in indicating the long-term neurologic prognosis in patients with a diagnosis of HIE was investigated. According to the results of all these studies the sensitivity of CBMRI in determining the long-term neurologic prognosis was found to be 38-100%, the specificity was found to be 43-100%, the positive predictive value was found to be 75-100% and the negative predictive value was found to be 67-82% (13)(14)(15)(16). In contrast to all these, Van Schie et al (17) reported that involvement of basal ganglia, thalamus, cortex and posterior limb of the internal capsule on MR imaging was not related to motor development at one year of age in patients with a diagnosis of HIE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, the value of conventional cranial MRI in indicating the long-term neurologic prognosis in patients with a diagnosis of HIE was investigated. According to the results of all these studies the sensitivity of CBMRI in determining the long-term neurologic prognosis was found to be 38-100%, the specificity was found to be 43-100%, the positive predictive value was found to be 75-100% and the negative predictive value was found to be 67-82% (13)(14)(15)(16). In contrast to all these, Van Schie et al (17) reported that involvement of basal ganglia, thalamus, cortex and posterior limb of the internal capsule on MR imaging was not related to motor development at one year of age in patients with a diagnosis of HIE.…”
Section: Discussionmentioning
confidence: 99%
“…With CBMRI brain lesions developed in infants with HIE can be determined at an early time (14). Therefore, imaging is recommended on the 2-8 th days (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Nine of the 32 studies in the meta-analysis included only surviving infants with HIE, which made their results potentially less relevant to questions about withdrawal of intensive care. [24][25][26][27][28][29][30][31][32] …”
Section: Populationmentioning
confidence: 99%
“…Some performed scans in the first days of life, 21,33-37 whereas others deferred imaging until after the first week. [24][25][26][27][28]38 However, the timing of imaging may be crucial if it is to be used in treatment-limitation decisions. 39 In infants with moderate or severe encephalopathy in cooling trials, the majority of deaths relating to withdrawal of treatment occurred in the first 3 or 4 days of life.…”
Section: Timingmentioning
confidence: 99%
See 1 more Smart Citation